Membership of editorial boards and rankings of schools with international business orientation - Chan, Kam C; Fung, Hung-Gay; Lai, Pikki (Journal of International Business Studies, 2005)
Using 4-year data (1990, 1994, 1998, and 2002), we have provided a ranking of schools with international business (IB) orientation based on the membership of editorial boards of 30 leading international business journals. Participation on the editorial boards of quality journals is highly selective, and should provide a quality indication of the schools. Both quality-unadjusted and adjusted board membership-based ranking are calculated in this study. Several interesting findings are worth noting. First, US schools play a significant leadership role among the leading IB programs. Second, the findings of this study also show the major contribution of non-US schools, which confirms the importance of the global nature of the IB discipline. Third, the top-ranked schools share a number of characteristics. Finally, the correlation among different ranking criteria can be low, particularly for the top-ranked schools, suggesting that care should be exercised in interpreting school ranking.